Sustainability Reporting Readiness in Indonesian Mining Companies - Ayu Puspitasari; Ika Nur Azmi (Universitas Kristen Maranatha, 2026)
Purpose – This study examines the readiness of Indonesian mining companies to adopt International Sustainability Standards Board (ISSB) reporting standards, specifically IFRS S1 and IFRS S2, while identifying influencing factors, key challenges, and best practices in transitioning from GRI-based to ISSB-based sustainability reporting. Design/Methodology/Approach – A qualitative exploratory approach was employed using systematic content analysis of sustainability and annual reports from 41 mining companies listed on the Indonesia Stock Exchange for fiscal year 2023. Analysis was conducted using NVivo 14 software with a deductive coding framework grounded in five ISSB pillars: Governance, Strategy, Risk Management, Metrics and Targets, and Climate-related Disclosures. Inter-coder reliability was confirmed through Cohen's Kappa coefficient (κ = 0.87). Results – Readiness levels vary significantly: 36.6% of companies demonstrate high readiness, 48.8% moderate, and 14.6% low. Critical gaps include limited ESG-financial integration (38% of total sample), scenario analysis capability (28% of total sample, with implementation concentrated among high readiness companies at 45%), and Scope 3 emissions disclosure (28% of total sample). Corporate governance strength, ESG human resource capacity, and technology infrastructure are the primary internal determinants of readiness. Research limitations/Implications – This study is limited to the mining sector using publicly available documents. Findings suggest regulators should develop phased ISSB adoption roadmaps, while companies must invest strategically in data infrastructure, ESG competencies, and cross-functional governance structures to ensure substantive, rather than merely symbolic, compliance. Keywords: Content Analysis, IFRS S1, IFRS S2, ISSB, Mining Sector, Sustainability Reporting